Is Entrepreneurial Success Predictable? An Ex-Ante Analysis of the Character-Based Approach - Marco Caliendo; Alexander S. Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper empirically analyzes whether the character-based approach, which is based on the personality structure and the human capital of business founders, allows prediction of entrepreneurial success. A unique data set is used consisting of 414 previously unemployed persons whose personal characteristics were screened by different methods, namely a one-day assessment center (AC) and a standardized questionnaire, before they launched their business. Results are partly unexpected: first, there is almost no correlation between the AC data and the questionnaire. Second, the predictive power of the AC data is slightly better than that of the questionnaire, but lower than expected in theory. Interestingly, for those subgroups where the AC data have low predictive power, the questionnaire does better. Third, when success is measured in terms of employees hired, the character-based approach is a poor predictor.
Keywords: J23; C13; M13; 330; Entrepreneurship; Psychological Assessment; Character-Based Approach; Success Prediction; Unternehmer; Selbstständige; Persönlichkeitspsychologie; Humankapital; Prognoseverfahren; Erfolgsfaktor; Theorie; Deutschland